A Preliminary Study to Evaluate the Topography of Narrow Surface Plate - Okasatria Novyanto; Eka Pratiwi (LIPI Press, Anggota IKAPI, 2015)
An approach method to evaluate the topography of narrow surface plate has been proposed. In some cases, the calibration of narrow surface plate would be very diffcult to carry out when using the electronic level, the autocollimator, or the laser interferometer. Therefore, the mechanical probe and universal measuring machine can be used as an alternative standard since they can substitute the function of measurements that was performed by the third measuring instruments. In this research, the narrow surface plate is represented by rectangular granite blocks of 600 mm x 90 mm in dimension, while the measuring standard is a mechanical probe of 0.01 μm in resolution and a universal measuring machine. The readings from the mechanical probe and universal measuring machine were analyzed by numerical methods to obtain information about the topography of the surface. As per the result, this proposed method can be applied to evaluate the topography of narrow surface plate, but this method still requires to be compared with the other method to validate the measurement procedure.Keywords: Surface ﬂatness, Numerical analysis, Mechanical probe